HUBUNGAN RIWAYAT DALAM KELUARGA DENGAN KEJADIAN DIABETES MELLITUS JUVENIL PADA ANAK DAN REMAJA DI KOMUNITAS IKADAR TAHUN 2022 - Siti Jubaedah (2023)
According to the International Diabetes Federation in 2019, as many as 463 million people worldwide aged 20-79 years have diabetes mellitus. The incidence of Type 1 DM covers 5-10% of the total incidence of diabetes mellitus and >90% occurs in children and adolescents. Data from IDAI showed that there were 1220 children with Type 1 DM. Many children with Type 1 DM were first diagnosed with Diabetic Ketoacidosis which is a complication of DMT1. Type DM is a chronic metabolic disorder characterized by hyperglycemia due to damage to pancreatic beta cells due to autoimmunity or idiopathic which causes little or no insulin to be produced. Genetic and environmental factors associated with the incidence of Type 1 DM. Family history increases the risk of Type 1 DM. The aim of this study was to determine the relationship between family history of DM and the incidence of Type 1 DM in children and adolescents. The type of research used is analytic observation with a case-control design. The sample used was 24 people for each group that met the inclusion and exclusion criteria and used primary data with a research instrument in the form of a questionnaire. The sampling technique uses total sampling. The data obtained were analyzed univariately and bivariately with the Ch-square test. The test results found that 16.7% in the case group had a family history of DM and 29.2% in the control group and in this study showed that there was no relationship between family history and the incidence of Type 1 DM (p = 0.492). Environmental factors as a cause of Type 1 DM were not studied in this study, so it is not known whether children with Type 1 DM get an environmental trigger or not.